PENGARUH RELATIONSHIP MARKETING TERHADAP KEPUASAN DAN LOYALITAS WISATAWAN YANG PERNAH MENGINAP DI HOTEL KABUPATEN SAMOSIR - Sianipar, Gloria J.M; Hutagaol, Susanna Mei Sifra; Simanjuntak, Agus Nakkok (UNIKA Santo Thomas, 2023)
This study aims to determine the effect of relationship marketing on the satisfaction and loyalty of tourists who have stayed at the hotel in Samosir Regency. Tourist satisfaction affects the loyalty of tourists who have stayed at hotels in Samosir Regency. The number of samples used in this study was 100 respondents using non-probability sampling. The results of this study indicate that relationship marketing has a positive and significant effect on the satisfaction of tourists who have stayed at the Samosir Regency Hotel, relationship marketing has a positive and significant effect on the loyalty of tourists who have stayed at the Samosir Regency Hotel, and Tourist satisfaction has a positive and significant effect on the loyalty of tourists who have stayed at the Samosir Regency Hotel. This research is expected to be a guide for marketers or hotel management to take advantage of relationship marketing in retaining consumers in the long term.